(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Treatment for traumatic lesions of the oral mucosa consists in the elimination of traumatic factors and bad habits. Medicinal herbs included in Kamistad and Stomatofit preparations have a disinfectant, bactericidal and anti-inflammatory effect, suppress the local inflammatory process, relieve irritation, reduce pain and burning, eliminate swelling and have a hemostatic effect. ’has a secret. The mucous membrane of the oral cavity is the initial part of the digestive tract, so it is exposed to various local influences, and also reflects all physiological and pathological processes occurring in the human body. A peculiarity of the oral cavity is that with any traumatic injury, the mucosa immediately becomes infected. The level of damage and clinical manifestations depend on the irritant, time and strength of exposure, as well as individual characteristics of the organism.